STRATEGI INOVASI KURIKULUM PENDIDIKAN ISLAM: KONSEPSI, KEBIJAKAN, DAN IMPLEMENTASINYA - Tatang Sudrajat; Agus Salim Mansyur; Qiqi Yulianti Zakiyah (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2020)
Abstract The education curriculum is an important part of the national education system. This has been regulated in several state / government regulations which are basically public policies. Educational innovation, especially the curriculum is needed to always be in accordance with the demands of the changing times. With library study and normative juridical research methods, it is known that the curriculum of Islamic education has been established and structured as part of the education policy system through various state / government regulations. This policy is a product and the authority of state / government institutions in responding to public interests in the form of a curriculum that is always in harmony with the changing times. The concepts of innovation in general and educational innovation, especially curriculum innovation is outlined by experts as part of the treasury of education. There are certain strategies that are owned by innovators and there are various challenges and problems in the process of curriculum innovation faced by innovators in their implementation. Keywords: strategy, education, curriculum, educational innovation Abstrak Kurikulum pendidikan merupakan salah satu bagian penting dari sistem pendidikan nasional. Hal ini telah diatur dalam beberapa regulasi negara/pemerintah yang pada dasarnya merupakan kebijakan publik. Inovasi pendidikan, khususnya kurikulum diperlukan agar selalu sesuai dengan tuntutan perkembangan jaman. Dengan metode penelitian yuridis normatif dan kajian kepustakaan, diketahui bahwa kurikulum pendidikan Islam telah ditetapkan dan tersusun sebagai bagian dari sistem kebijakan pendidikan melalui berbagai regulasi negara/pemerintah. Kebijakan ini merupakan produk dan otoritas lembaga negara/pemerintah dalam merespon kepentingan publik berupa kurikulum yang selalu selaras dengan perkembangan jaman. Konsep inovasi secara umum dan inovasi pendidikan, khususnya inovasi kurikulum diuraikan oleh para ahli sebagai bagian dari khasanah ilmu pendidikan. Ada strategi tertentu yang dimiliki para inovator serta terdapat berbagai tantangan dan permasalahan dalam proses inovasi kurikulum yang dihadapi para inovator dalam implementasinya. Kata kunci : strategi, pendidikan, kurikulum, inovasi pendidikan